L' opinion allemande sous le nazisme : Bavière 1933-1945 - Kershaw, Ian; Dauzat, Pierre-Emmanuel (Paris : CNRS, 2002)
Bibliotheek François Vercammen
Oorspronkelijke titel: Popular opinion and political dissent in the Third Reich
Frans
Monografie
Keywords: Nazisme; Duitsland; Beieren